1999
DOI: 10.2134/jeq1999.00472425002800050001x
|View full text |Cite
|
Sign up to set email alerts
|

Determining Travel Time and Stream Mixing using Tracers and Empirical Equations

Abstract: Water-supply managers need adequate warning to protect water supplies if a contaminant is spilled in an upgradient tributary. The city of Lincoln draws water from alluvium associated with the Platte River near Ashland, eastern Nebraska. Using constant-rate injection methods and a conservative tracer, travel time and degree of mixing of contaminants in the Elkhorn and Platte Rivers were evaluated in 1995 and 1996. The results indicate that, for flows of 584 to 162 m 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The study area, defined as the 100‐year floodplain plus a 1.5‐km buffer at both sides of the Platte River, is an area of ∼2600 km 2 in eastern Nebraska from near Columbus to the Platte River's confluence with the Missouri River (Figure 1). The drainage area of the Platte River in Nebraska is 106,000 km 2 , with a mean annual flow of ∼200 m 3 /s at Plattsmouth (Verstraeten et al 1999a). The river generally is a gaining river except for a small area upgradient.…”
Section: Settingmentioning
confidence: 99%
“…The study area, defined as the 100‐year floodplain plus a 1.5‐km buffer at both sides of the Platte River, is an area of ∼2600 km 2 in eastern Nebraska from near Columbus to the Platte River's confluence with the Missouri River (Figure 1). The drainage area of the Platte River in Nebraska is 106,000 km 2 , with a mean annual flow of ∼200 m 3 /s at Plattsmouth (Verstraeten et al 1999a). The river generally is a gaining river except for a small area upgradient.…”
Section: Settingmentioning
confidence: 99%
“…In many surface water applications, rhodamine WT is considered ''reasonably stable'' with a ''low sorptive tendency'' [Wilson et al, 1986]. As such, numerous investigators have employed rhodamine WT as a tracer and considered it to be nominally conservative [e.g., Verstraeten et al, 1999;Atkinson and Davis, 2000;De Smedt et al, 2005;Rowinski et al, 2008]. Investigators of groundwater systems, in contrast, have recognized the reactive properties of rhodamine WT, and have employed it as a nonconservative surrogate for organic contaminants subject to sorption [Sabatini and Austin, 1991;Everts and Kanwar, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…The travel time from atrazine use areas to drinking water intakes is easily within that time span. Indeed, Verstraeten et al . (1999) has shown that only 8.2 to 13.2 h are required for the leading edge of a chemical plume to travel over 56 km in the Elkhorn River near Waterloo to the Platte River at Ashland (the location of the Lincoln, NE water supply intake).…”
Section: Resultsmentioning
confidence: 99%